First Report of HPV Genotyping and Distribution in People Living with and Without HIV from Iran and the Middle East - Maleki, Faezeh; Farahmand, Mohammad; Keyvani, Hossein (Current HIV Research, 2025)
AimsIn people living with human immune deficiency (PLHIV), the rates of human papillomavirus (HPV) infection, mixed types, and high-risk (HR) strains increase, while the virus clearance does not occur. Here, we report HPV genotyping in PLHIVs from Iran and the Middle East region for the first time.MethodsHPV genotyping in referring individuals from different provinces to our laboratory was evaluated over 2023-2024. For this, the HPV types in specimens were detected through the INNO-LiPA HPV genotyping kit. Statistical analysis was conducted with a 95% confidence interval (95%CI) and P < 0.05. Accordingly, 481 subjects from various provinces participated in this study.ResultsThe rate of HPV infection was 45.7%, of which 14% were HIV-infected women referred from all provinces. The most prevalent types included 6, 51, and 18, but not 16 HR types. Mixed infections in dually infected women were significantly more than in HPV-infected ones. The HPV+/HIV+ subgroup had the lowest median age. The prevalence of HPV types and mixed infection in PLHIVs was congruent with the previous reports, except for the low rate of type 16 infection, perhaps due to the healthy nature of our subjects. Only HIV+/HPV+ cases' age was similar to the previous reports, perhaps because of sample collection and study designs. Among all factors, age and gender affected the HPV type distribution notably.ConclusionThe current study corroborated the results of many prior reports, demonstrating the considerable impact of HIV status on HPV distribution. The authors recommend implementing a national HPV vaccination and more comprehensive reports of HPV genotyping in PLHIVs.
Keywords: HPV vaccination